Peran Orang Tua dalam Meningkatkan Kehidupan Menggereja OMK di Stasi Santo Blasius Kalasey Paroki Santo Fransiskus Xaverius Mokupa - Bernadina Waha Labuan; Adrianus Dalia (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2023)
The purpose of this study was to find out the role of parents in improving the life of the OMK church at St. Blasius Kalasey Station, the supporting factors and inhibiting factors for the role of parents in improving church life, as well as the efforts of parents to improve the OMK church life. This research uses a descriptive research technique or type with a qualitative approach. Data collection techniques used in this study are observation, interviews and documentation. The main instrument in this research is the writer himself. The conclusion of this study consists of three parts, namely First: parents realize the importance of the role of parents in improving church life but the role of parentsstill not implemented optimally because there are things that become obstacles, both from parents and from OMK. Second: the factors that support or hinder the role of parents, for example the time factor which can be a supporting or inhibiting factor, because the lack or sufficient time for parents and children can influence whether or not the role of parents is optimal in improving their child's church life. Third: the efforts of parents who continue to guide their children in a way that they think is effective in terms of improving church life.